Peningkatan Kompetensi Evaluasi Pembelajaran Berbasis Teknologi Pada Guru SD di Kota Surakarta - idam atmojo (Jurnal Pendidikan Dasar, 2019)
Abstract. Technology is an inseparable part of human activities in this era. The era that is referred to as the era of disruption, the actual form of implementation is the Industrial Revolution 4.0 and in education referred to as Education 4.0. Because all aspects of life must be able to adapt or even accelerate. The existence of Google Form Assisted Learning Evaluation in the school environment, especially primary schools in an effort to optimize the results of each implementation of the learning process is very important, therefore training and assistance are needed to help teachers master the material on the Google Form Assisted Authentic Modeling Training both in terms of manufacturing and use. Subjects in this service consist of elementary school teachers in the administrative area of the city of Surakarta. The method used in this training is Workshop, Practice, and Implementation. Data collection techniques using test techniques. The analysis technique used is pre test and post test. holding aworkshop on making evaluations and administration based on google forms can improve the ability of teachers to prepare HOTs-based Questions that will be used in implementing learning.